Affine invariant conditions for the inexact perturbed Newton method - Emil Cătinaş (Journal of Numerical Analysis and Approximation Theory, 2002)
The high convergence orders of the inexact Newton iterates were characterized by Ypma in terms of some affine invariant conditions. Using these results, we obtain affine invariant characterizations for the convergence orders of the inexact perturbed Newton iterates.